Election Gifting and the Ordeal of Democracy in Nigeria - Adekola, Adeagbo A.; Olumide, Omodunbi O. (European Scientific Journal, ESJ, 2019)
Over-time, researchers have failed to show how citizens share, if not all, a part of the blame in Nigeria’s failing democracy. Through election gifting, the community of voters in Nigeria have been selling their commonwealth to politicians who should not be anywhere close to power. Using secondary sources of data and relying on Robert Dahl’s theory of democracy, the paper argues that since the people are the custodians of the political mandate in any democracy, they should be held accountable when there is a problem. The paper further identifies the history, effect, scope, and predisposing factors of election gifting in Nigeria. This paper focuses on the fact that the non-evaluative and clientelist approach to democracy are the reason for the sad realities in Nigeria and concludes that only the engagement in a civil society can revive Nigeria’s failing democracy.